2016
DOI: 10.1002/chem.201603753
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoid‐Based Self‐Healing Supramolecular Polymer Hydrogels Formed by Host–Guest Interactions

Abstract: Pentacyclic triterpenoids, a class of naturally bioactive products having multiple functional groups, unique chiral centers, rigid skeletons, and good biocompatibility, are ideal building blocks for fabricating versatile supramolecular structures. In this research, the natural pentacyclic triterpenoid glycyrrhetinic acid (GA) was used as a guest molecule for β-cyclodextrin (β-CD) to form a GA/β-CD (1:1) inclusion complex. By means of GA and β-CD pendant groups in N,N'-dimethylacrylamide copolymers, a supramole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 60 publications
0
33
0
Order By: Relevance
“…In our previous study, we reported a 1:1 inclusion complexation of GA with β‐CD (the binding constant K a =1.59×10 3 m −1 ). In addition, the 1 H NMR spectrum further confirmed the complexation of β‐CD with the polymer containing GA pendants.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In our previous study, we reported a 1:1 inclusion complexation of GA with β‐CD (the binding constant K a =1.59×10 3 m −1 ). In addition, the 1 H NMR spectrum further confirmed the complexation of β‐CD with the polymer containing GA pendants.…”
Section: Resultsmentioning
confidence: 95%
“…Statistical copolymers poly(DMA‐GA‐ x %) ( x =0, 1, 2, 4) bearing GA pendants with different contents were synthesized by means of a free‐radical polymerization of N , N′ ‐dimethylacrylamide (DMA) with GA‐based methacrylate according to our previous work (see the Supporting Information). Their molecular weights, polydispersity indexes (PDIs), and yields are summarized in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid alloys composed of gallium are also ideal candidates for creating conductive circuits within elastomeric substrates, which spontaneously can self‐heal electrical and mechanical defects imposed on them during wear and tear . A recent study accomplished this daring task through a simple system composed of a hollow self‐healing polymer (Reverslink@) into which EGaln was injected.…”
Section: Conductive Polymer Compositesmentioning
confidence: 99%
“…Owing to the biocompatibility, structural rigidity, chirality, self‐assembling capacity, and easy functionalization of hydroxyl and carboxylic groups, GA has served as a useful hydrophobic building block for functional materials . For example, Mezzenga and co‐workers reported that the GA moiety afforded suitable hydrophobic forces for fabricating helical fibers containing three‐folded hybrid nanomaterials of glycyrrhizic acid; our group found that GA pendants in poly(dimethylacrylamide‐ ran ‐GA) could form the host–guest complex with β‐cyclodextrin (β‐CD) in poly(dimethylacrylamide‐ ran ‐CD), thus resulting in a self‐healable polymeric supramolecular hydrogel . Clearly, GA is an ideal choice as the hydrophobic pendant in amphiphilic copolymers.…”
Section: Introductionmentioning
confidence: 99%